2020
DOI: 10.1103/physreve.101.022101
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of surface roughness in a one-dimensional Kardar-Parisi-Zhang growth process

Abstract: Control of generically scale-invariant systems, i.e., targeting specific cooperative features in nonlinear stochastic interacting systems with many degrees of freedom subject to strong fluctuations and correlations that are characterized by power laws, remains an important open problem. We study the control of surface roughness during a growth process described by the Kardar-Parisi-Zhang (KPZ) equation in (1 + 1) dimensions. We achieve the saturation of the mean surface roughness to a prescribed value using no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 29 publications
2
19
2
Order By: Relevance
“…Regarding experimental studies of the KPZ equation via liquid crystal turbulence, we refer to [24][25][26]. Recent numerical treatment of the KPZ equation is shown in, e.g., [27][28][29][30][31]. From a mathematical point of view, in [32] a spacetime discretization scheme for the equivalent Burgers equation has been proposed and its convergence, albeit in a weak distributional sense (which seems to be the best to be expected), has been rigorously proven.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding experimental studies of the KPZ equation via liquid crystal turbulence, we refer to [24][25][26]. Recent numerical treatment of the KPZ equation is shown in, e.g., [27][28][29][30][31]. From a mathematical point of view, in [32] a spacetime discretization scheme for the equivalent Burgers equation has been proposed and its convergence, albeit in a weak distributional sense (which seems to be the best to be expected), has been rigorously proven.…”
Section: Introductionmentioning
confidence: 99%
“…We choose b n (x) = exp (−i2πnx/L), as in our previous study (see Ref. [24] for details); the number of actuators is 2n c . The controlled equation ( 3) is solved with periodic boundary conditions,…”
Section: Linearly Controlled Kpz Equationmentioning
confidence: 99%
“…In our previous work [24], we have shown that removing the non-linearity with different cutoff Fourier modes n c will enable the system to saturate at the desired roughness, but this significantly alters the growth dynamics. However, in order to implement a control scheme that does not change the intrinsic dynamics, it is essential to consider the effect of the non-linearity at all times.…”
Section: Linearly Controlled Kpz Equationmentioning
confidence: 99%
See 2 more Smart Citations